Probabilistic Physiologically Based Pharmacokinetic Model for Penicillin G in Milk From Dairy Cows Following Intramammary or Intramuscular Administrations. (21st March 2018) - Li, Miao; Gehring, Ronette; Riviere, Jim E; Lin, Zhoumeng
Abstract: Penicillin remains one of the most frequently identified violative drug residues in food-producing animals. The predominant violations of penicillin were found in cull dairy cows. In the United States, procaine penicillin G is approved to be used in dairy cows through intramuscular (IM) and intramammary (IMM) administrations. Physiologically based pharmacokinetic (PBPK) models are useful tools to predict withdrawal intervals and tissue residues of drugs in food animals to ensure food safety, especially for extralabel drug use due to the scarcity of experimental data after extralabel administrations. Currently, no PBPK model is available to predict penicillin concentrations in milk. A population PBPK model with a physiologically based compartment for the mammary gland was established for penicillin G in dairy cows. The model predicted the tissue and milk residues well based on comparison with data from previous pharmacokinetic studies. The predicted milk discard interval of procaine penicillin G administered at 10 times the label dose for 3 repeated IM administrations was 182 h, and 122 h at 4 times the label dose after 3 repeated IMM infusions. Predicted results showed that even 4 times label dose did not lead to violative tissue residues in healthy dairy cows with IMM infusions. The predominant violations found in cull dairy cows may be caused by altered pharmacokinetics due to mastitis, other diseases, and/or interactions with other drugs, which have impacts on penicillin distribution and elimination. The current PBPK model can help predict milk discard interval for penicillin following extralabel use through IM and IMM administrations.